2010
DOI: 10.1590/s1519-38292010000100011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores de risco para anemia em crianças pré-escolares do Estado de Alagoas, Brasil

Abstract: O b j e c t i v e : t o e s t i m a t e t h e p re v a l e n c e a n d e s t ablish risk factors associated with anemia in children in the Brazilian State of Alagoas. M e t h o d s : a c ro s s -s e c t i o n a l s t u d y w i t h a p ro b abilistic sample of 666 children aged between 6 and 60 m o n t h s . A n t h ro p o m e t r i c , e n v i ro n m e n t a l , d e m o - s e d i d e n t i f y c o r re l a t i o n s a n d t h e χ 2 t e s t t o a n a l y z e a s s o c i a t i o n s b e t w e e n t h e c a t e g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
0
12
0
7
Order By: Relevance
“…Outros estudos nacionais localizados apontam prevalências de anemia que oscilam de 36,4% a 47,8% entre menores de cinco anos 4,5,6,7 e de 47,8% a 54% entre menores de três anos 8,9 . Além disso, contrariamente à tendência de redução da desnutrição infantil nas últimas décadas, a anemia parece apresentar tendência temporal de aumento entre as crianças brasileiras 10 .…”
Section: Introductionunclassified
“…Outros estudos nacionais localizados apontam prevalências de anemia que oscilam de 36,4% a 47,8% entre menores de cinco anos 4,5,6,7 e de 47,8% a 54% entre menores de três anos 8,9 . Além disso, contrariamente à tendência de redução da desnutrição infantil nas últimas décadas, a anemia parece apresentar tendência temporal de aumento entre as crianças brasileiras 10 .…”
Section: Introductionunclassified
“…Studies in different Brazilian municipalities found similar results, with anemia being significantly associated with more individuals per household and worse education level of the family head 20,21 . However, in this study, these variables were not associated with anemia.…”
Section: Security Severe Insecuritymentioning
confidence: 57%
“…It is important to mention that most studies on this topic in Brazil have investigated iron-deficiency anemia [2,5,7,8,12,[25][26][27][28][29], and few have evaluated these Value refers to 1 minimum wage -R$540,00.…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of childhood anemia has been associated with several factors: children aged ≤5 years [6,8,11,12], low family income [5,8,13], high household density [5,[11][12][13], low maternal education level [7,11,13,14], poor housing conditions, lack of adequate sanitation [5,7,12], and some dietary variables such as low iron [5,8,9,12] and protein [5] intake.…”
Section: Introductionmentioning
confidence: 99%